Enhancing connectivity/mobility in WBAN applications through detachable wearable multi-band MIMO antenna - Saeidi, Tale; Saleh, Sahar; Timmons, Nick Francis; Karamzadeh, Saeid; Al Gburi, Ahmed Jamal Abdullah; Razzaz, Faroq (Institute of Physics, 2024)
The connectivity and mobility of a miniaturized multi-band four-port textile leaky wave multiple-input multiple-output (MIMO) antenna designed on a layer of denim (ϵr = 1.6, tanδ = 0.006) is enhanced by integrating it with two detachable spiral buttons designed on circular PTFE substrate (ϵr = 2.1, tanδ = 0.001). The connectivity and mobility enhancement of the proposed antenna is evaluated in terms of radiation and diversity parameters. Nested hexagonal split rings behind the buttons, U-shaped slots on textiles, a comb-shaped neutralization network, and an aperture-coupled feed technique are utilized. The unique structure of the buttons on a rigid substrate and the leaky wave antenna on the textile and their integration, the periodic nested elliptical and circular split ring resonators (CSRRs) slots on the aperture coupled to ground, are to expand the connectivity and mobility of the proposed MIMO antenna by offering multiple bands, higher isolation, broadside radiation, and low specific absorption rate (SAR). The leaky wave and button antennas have dimensions of 40 × 30 × 1 mm3 and a diameter of only 13 mm, respectively. The operational bands are 0.86-2.75 GHz, 2.9-4.85 GHz, 5.75-6.15 GHz, and 8-9.85 GHz, covering the L, C, S, and X bands. Additionally, diversity performance is evaluated by defining the envelope correlation coefficient (ECC), diversity gain (DG), Channel Capacity Loss (CCL), and mean effective gain (MEG). The simulation and measurement findings are in good agreement. Following that, it offers a maximum gain of 8.25 dBi, low SAR (<0.05), an ECC below 0.05, DG above 9.85 dB, CCL< 0.25 bits/s/Hz, MEG <−3 dB, Circular polarization (CP), and strong isolation (>22 dB) between every two ports. These features make the proposed antenna an ideal option for MIMO communications and suitable for wireless local area network (WLAN) and fifth-generation (5G) communications.